Mental Health Literacy in Education: Reducing Stigma and Building Social Awareness Among High School Students - Novianty Djafri; Usharani Khuntia (Educational Dynamics: International Journal of Education and Social Sciences, 2024)
Mental health stigma and low Mental Health Literacy (MHL) remain major challenges affecting the well-being of high school students, often preventing them from seeking professional help and contributing to psychological distress. This study aimed to evaluate the effectiveness of a school-based mental health literacy workshop in reducing stigma and enhancing students’ knowledge and social awareness. A quantitative experimental design with pre-test and post-test measurements was employed, involving high school students selected through purposive sampling. The intervention consisted of a face-to-face workshop covering basic mental health concepts, common adolescent disorders, strategies to seek professional support, and approaches to provide peer support. Data were collected using standardized attitudinal surveys and analyzed with paired t-tests. The results indicated a significant reduction in mental health stigma and a substantial increase in mental health knowledge. Additionally, students demonstrated improved understanding of mental health concepts, enhanced ability to recognize common disorders, greater awareness of help-seeking strategies, and increased empathy toward peers experiencing mental health challenges. These findings suggest that interactive workshops are effective in promoting both individual literacy and a supportive school environment. In conclusion, integrating mental health literacy programs into school curricula provides a sustainable strategy to reduce stigma, foster inclusive attitudes, and equip adolescents with the knowledge and social skills necessary for improved mental well-being.